Accuracy of prehospital clinicians' perceived prognostication of long-term survival in critically ill patients: a nationwide retrospective cohort study on helicopter emergency service patients - Heino Anssi; Björkman Johannes; Tommila Miretta; Iirola Timo; Jäntti Helena; Nurmi Jouni (BMJ PUBLISHING GROUP, 2022)
Objectives Prehospital critical care physicians regularly attend to patients with poor prognosis and may limit the advanced therapies. The aim of this study was to evaluate the accuracy of poor prognosis given by prehospital critical care clinicians.
Design Cohort study.
Setting We performed a retrospective cohort study using the national helicopter emergency medical services (HEMS) quality database.
Participants Patients classified by the HEMS clinician to have survived until hospital admission solely because of prehospital interventions but evaluated as having no long-term survival by prehospital clinician, were included.
Primary and secondary outcome The survival of the study patients was examined at 30 days, 1 year and 3 years.
Results Of 36 715 patients encountered by the HEMS during the study period, 2053 patients were classified as having no long-term survival and included. At 30 days, 713 (35%, 95% CI 33% to 37%) were still alive and 69 were lost to follow-up. Furthermore, at 1 year 524 (26%) and at 3 years 267 (13%) of the patients were still alive. The deceased patients received more often prehospital rapid sequence intubation and vasoactives, compared with patients alive at 30 days. Patients deceased at 30 days were older and had lower initial Glasgow Coma Scores. Otherwise, no clinically relevant difference was found in the prehospital vital parameters between the survivors and non-survivors.
Conclusions The prognostication of long-term survival for critically ill patients by a prehospital critical care clinician seems to fulfil only moderately. A prognosis based on clinical judgement must be handled with a great degree of caution and decision on limitation of advanced care should be made cautiously.